Estetika Resepsi Dan Intertekstualitas : Perspektif Ilmu Sastra Terhadap Tafsir Al-Qurâan - Sulaeman, Otong (Sekolah Tinggi Filsafat Islam Sadra, 2015)
Abstract : The Quranic interpretation is an effort to explain the meaning of the Quranic verses. In literary studies, the Quranic interpretative attempt is an interpreterâs reception aestethics towards the Quranic verses. In another side, the interpreter (mufasir) is, during his effort of interpreting the Quran, necessarly influ-enced by the other texts he or she has ever read. The process of the interpreterâs being influenced by the other texts while interpreting the Quran is, in the literary theory, called intertextuality. Thus, there is a very close relation between the Quranic interpretation and literary sciences.Keywords : literary science, structuralism of science, pragmatic approach, reception aesthetics, intertextuality, the Quran, interpretation, hadith, history.Â Abstrak : Tafsir al-Qurâan adalah upaya untuk menjelaskan maksud dari ayat-ayat al-Qurâan. Dalam perspektif ilmu-ilmu sastra, upaya untuk menafsirkan al-Qurâan adalah bentuk estetika resepsi mufasir (penafsir) ter-hadap ayat-ayat al-Qurâan. Di sisi lain, saat menafsirkan ayat-ayat al-Qurâan, mufasir pastilah dipengaruhi oleh teks-teks lain yang pernah menjadi sumber bacaannya. Proses dipengaruhinya mufasir oleh teks bacaan lain saat menafsirkan al-Qurâan ini dalam konteks ilmu-ilmu sastra disebut intertekstualitas. Dengan demikian, ada hubungan yang sangat erat antara tafsir al-Qurâan dengan ilmu-ilmu sastra.Kata-Kata Kunci : ilmu sastra, strukturalisme ilmu, pendekatan pragmatik, estetika resepsi, intertekstualitas, al-Qurâan, tafsir, hadis, sejarah